2021
DOI: 10.1186/s13098-021-00713-9
|View full text |Cite
|
Sign up to set email alerts
|

Advances in GLP-1 treatment: focus on oral semaglutide

Abstract: Background There is currently a large arsenal of antidiabetic drugs available to treat type 2 diabetes (T2D). However, this is a serious chronic disease that affects millions of adults worldwide and is responsible for severe complications, comorbidities, and low quality of life when uncontrolled due mainly to delays in initiating treatment or inadequate therapy. This review article aims to clarify the therapeutic role of the oral formulation of the glucagon-like peptide 1 receptor agonist (GLP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
(184 reference statements)
0
10
0
2
Order By: Relevance
“…As shown in this work, FCS would self-assemble with various therapeutic proteins to form stable nanocomplexes, which are lyophilized in the presence of mannitol and then loaded into enteric capsules for oral feeding (Figure a). According to the pharmacokinetic behavior of IgG after oral administration, oral delivery of an antibody with the help of FCS was realized, reaching a bioavailability as high as 4.73% in mice, in marked contrast to that of reported oral peptide drugs such as Mycapssa and Rybelsus (bioavailability of 0.25–1%). , We found that oral delivery of checkpoint antibodies such as αPD1 or αCTLA4 could indeed effectively activate the immune system. Using a 5-fold dose of the intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 71%
“…As shown in this work, FCS would self-assemble with various therapeutic proteins to form stable nanocomplexes, which are lyophilized in the presence of mannitol and then loaded into enteric capsules for oral feeding (Figure a). According to the pharmacokinetic behavior of IgG after oral administration, oral delivery of an antibody with the help of FCS was realized, reaching a bioavailability as high as 4.73% in mice, in marked contrast to that of reported oral peptide drugs such as Mycapssa and Rybelsus (bioavailability of 0.25–1%). , We found that oral delivery of checkpoint antibodies such as αPD1 or αCTLA4 could indeed effectively activate the immune system. Using a 5-fold dose of the intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 71%
“…Semaglutide is the latest generation GLP-1RA analogue for chronic weight management in adults with obesity or overweight with at least one weight related comorbidity, as an adjunct to lifestyle intervention. Similar to liraglutide, semaglutide offers the unique advantage of glycaemic regulation by stimulating insulin secretion and decreases glucagon secretion which improves glycaemic control (65) . Semaglutide was initially approved for T2D therapy use of up to 1.0mg via subcutaneous injection (66) or up to 14mg once-daily oral administration in 2017 and 2019, respectively, by the EMA and FDA (67) .…”
Section: Semaglutidementioning
confidence: 99%
“…90% of these cases are represented by type 2 DM, although more than 50% of them did not have access to early diagnosis and adequate treatment. Furthermore, 374 million people have insulin resistance (IR) which increases their chance of developing type 2 DM [18,24]. Obesity is considered as a lifelong progressive disease with periods of remission and recurrences that plays a significant role in the evolution of DM and its clinical manifestations [54].…”
Section: Introductionmentioning
confidence: 99%